Immunofluorescence and Cytochemical Studies of Visna Virus in Cell Culture - Harter, D. H. (1967)
Sequential morphological changes occurring in sheep choroid plexus cells infected with visna virus were studied by direct immunofluorescence, acridine orange, and hematoxylin and eosin staining methods. Specific immunofluorescence was first detected in the perinuclear cytoplasm of solitary cells 24 hr after infection. As the infection progressed, viral antigen appeared in an increasing number of cells, and rounded globular cells with long slender processes harboring intense fluorescence were seen. Nuclear fluorescence was not observed in infected monolayers. Polykaryocytes formed within 6 hr after inoculation due to the direct cell-fusing effect of the virus inoculum did not show specific fluorescence. Viral antigen was found, however, in the cytoplasm of multinucleated giant cells in cover slips harvested after new infective virus had been released, and later in the course of infection circular fluorescent inclusions were seen in the cytoplasm of polykaryocytes. Comparable eosinophilic inclusions were observed in hematoxylin and eosin preparations, and acridine orange staining of infected monolayers demonstrated similar inclusions which fluoresced with the color characteristic of single-stranded nucleic acid and were susceptible to digestion with ribonuclease. Visna virus appears to be a ribonucleic acid virus which replicates in the cytoplasm.